Zirconium complexes supported by an N-perfluoro-arylated diamidopyridyl ligand: synthesis of hydrazinediido complexes - Scholl, Solveig A.; Plundrich, Gudrun; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2013)
The N-perfluoro-phenylated pyridyldiamine H2N2PFPNpy (1) has been prepared by a palladium-catalyzed coupling of hexafluorobenzene and the diamine (H2NCH2)2C(CH3)(2-C5H4N) using the palladacycle trans-di(μ-acetato)bis[o-(di-o-tolylphosphino)benzyl]palladium(II) as catalyst. Reactions of H2N2PFPNpy and Zr(NMe2)4 at room temperature or 90 °C led to the complexes [(NPFPN2TFAPNpy)ZrF(NMe2)] (2) and [(N2TFAPNpy)ZrF2] (3) in which one or two dimethylamido groups replaced one or two ortho fluorine atoms of the pentafluorophenyl groups in the ligand. Reaction of Me3SiX (X = Cl, I) with [(N2TFAPNpy)ZrF2] (3) resulted in the formation of mixed halogenated complexes [(N2TFAPNpy)ZrFI] (4) and [(N2TFAPNpy)ZrFCl] (5) in which the axially bound fluorido ligand is substituted. Reaction of [(N2TFAPNpy)ZrF2] (3) with LiNHNPh2 afforded the monohydrazido(1−) complex [(N2TFAPNpy)ZrF(NHNPh2)] (6) which was converted to the dimeric fluoro-potassium bridged hydrazinediido complex [Zr(N2TFAPNpy)FNNPh2K]2 (7) using KHMDS. The corresponding reaction with LiHMDS yielded the monomeric, donor free complex [Zr(N2TFAPNpy)NNPh2] (8).